An Islamic Legal Perspective on Fatherlessness and the Responsibility to Realize Family Resilience: A Case Study of Tanjungbalai City - Elvina Jahwa; Sugeng Wanto (Pascasarjana IAIN Metro, 2026)
This study examines the phenomenon of fatherlessness from an Islamic legal perspective and explores its implications for family resilience, as well as how fathers’ responsibilities are enacted within households in Tanjungbalai City. Employing a qualitative design that integrates yuridical-normative and sociological approaches, the research draws on primary data from in-depth interviews with affected families and community leaders and on secondary sources consisting of Islamic legal literature and relevant policy documents. Findings indicate that Islamic law positions the father as a central figure (qawwam) charged with provision, caregiving, moral formation, and spiritual guidance. Empirical evidence from the field reveals prevalent forms of fatherlessness that are functional and emotional in nature, where fathers remain biologically present but are insufficiently engaged in psychosocial caregiving. This gap weakens family resilience across economic, socio-psychological, and spiritual dimensions, although some households demonstrate adaptive capacities owing to maternal roles and local social support networks. The study recommends strengthening fathers’ engagement through targeted parenting education, community-based interventions, and family-friendly policies, and calls for coordinated action by families, religious institutions, and governmental agencies to safeguard children’s rights and bolster family resilience.